2019
DOI: 10.33235/va.5.1.4-7
|View full text |Cite
|
Sign up to set email alerts
|

“Just in case”. Use of large-bore peripheral intravenous catheters in parturient women: A global study

Abstract: Link to published version https://journals.cambridgemedia.com.au/va/volume-5-issue-1/just-case-use-large-boreperipheral-intravenous-catheters-parturient-women-global-study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Relatively large‐gauge PIVCs were ubiquitously reported, with all women in our study receiving either a 16 or 18 g PIVC, consistent with previous local (Webster et al., 2018) and international research (Webster et al., 2019). In our study, PIVCs were inserted predominantly for medication or IV fluid administration: over half being in the back of the hand.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Relatively large‐gauge PIVCs were ubiquitously reported, with all women in our study receiving either a 16 or 18 g PIVC, consistent with previous local (Webster et al., 2018) and international research (Webster et al., 2019). In our study, PIVCs were inserted predominantly for medication or IV fluid administration: over half being in the back of the hand.…”
Section: Discussionsupporting
confidence: 90%
“…This study sought to describe and explore the practices of maternity healthcare professionals' decision‐making and practices about PIVC selection and use during labour and birth and measure the pain associated with this common procedure from the perspective of birthing women. It demonstrated that this somewhat ‘simple’ procedure is often unsuccessful (34%) and painful (3.3/10) (Webster et al., 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation